Phylogeographic pattern and extensive mitochondrial DNA divergence disclose a species complex within the Chagas disease vector Triatoma dimidiata (2013)
ABSTARCT: Previous studies have shown that "bioequivalent" generic products of vancomycin are less effective in vivo against Staphylococcus aureus than the innovator compound. Considering that suboptimal bactericidal effect has been associated with emergence of resistance, we aimed to assess in vivo the impact of exposure to innovator and generic products of vancomycin on S. aureus susceptibility. A clinical methicillin-resistant S. aureus (MRSA) strain from a liver transplant patient with persistent bacteremia was used for which MIC, minimum bactericidal concentration (MBC), and autolytic properties were determined. Susceptibility was also assessed by determining a population analysis profile (PAP) with vancomycin concentrations from 0 to 5 mg/liter. ICR neutropenic mice were inoculated in each thigh with ∼7.0 log(10) CFU. Treatment with the different vancomycin products (innovator and three generics; 1,200 mg/kg of body weight/day every 3 h) started 2 h later while the control group received sterile saline. After 24 h, mice were euthanized, and the thigh homogenates were plated. Recovered colonies were reinoculated to new groups of animals, and the exposure-recovery process was repeated until 12 cycles were completed. The evolution of resistance was assessed by PAP after cycles 5, 10, 11, and 12. The initial isolate displayed reduced autolysis and higher resistance frequencies than S. aureus ATCC 29213 but without vancomycin-intermediate S. aureus (VISA) subpopulations. After 12 cycles, innovator vancomycin had significantly reduced resistant subpopulations at 1, 2, and 3 mg/liter, while the generic products had enriched them progressively by orders of magnitude. The great capacity of generic vancomycin to select for less susceptible organisms raises concerns about the role of therapeutic inequivalence of any antimicrobial on the epidemiology of resistance worldwide.